THE INFLUENCE OF GREEN MARKETING ON CONSUMER BUYING BEHAVIOR (Study at The Body Shop Manado) - Mantiaha, Gratia F. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Now there are so many companies that use environmental issues as their marketing strategy. This marketing strategy is known as Green Marketing. The attention to environmental issues can be seen from the increasing in environmentally awareness markets. Many companies are choosing green marketing strategy company that has a great opportunity to increase sales. With Green Marketing, companies have to compete and prove that their products are produced after going through the stages of environmental management efforts and safe to use. Data collection method of this is using a questionnaire. Multiple regression analysis was used to test the stated hypothesis and to find out the influence of dependent variable with independent variables. The respondents of this research are 40 respondents. Green marketing in this research is represented by green product and green promotion. The result shows that these two variables of green marketing have positive significant influence on consumer buying behavior simultaneously. Partially, green product has no significant influence on consumer buying behavior. While green promotion has significant on consumer buying behavior. The Body Shop should be consistent about their quality of product that already known as a good cosmetic product. Management should guarantee their product as a safe product for consumer’s skin. Keywords: green marketing, green product, green promotion, consumer buying behavior